Risk Aversion, Risk, and the Duration of Unemployment - Feinberg, Robert M. (The Review of Economics and Statistics, 1977)
A jobseeker's attitudes towards risk and his perception of the risk inherent in the labor market he is searching have been shown to have a theoretical effect on his expected duration of search, when he is assumed to be searching for jobs in an optimal fashion.' However, no empirical research has adequately tested for these predicted effects.2 This article presents estimates of a reduced-form equation derived from the job search theory3 and tests the following two hypotheses: (1) as the standard deviation of the distribution of potential wage offers increases, an individual's expected duration of unemployment will increase, ceteris pariblis; (2) an individual who is more risk averse than another will have a shorter expected duration of unemployment, ceteris paribbls. The empirical results presented here tend to support both of these hypotheses. Both Kohn and Shavell (1974) and Pissarides (1974) prove, within models of optimal job search, that the more risk averse a job seeker, the lower he will set his minimum acceptable, or reservation, wage. The reservation wage is set to equate the marginal cost of an additional period of search with the expected marginal return from search; any job offer exceeding this wage is accepted and unemployment terminates.4 Determinants of the individual's reservation wage include costs of search, his risk preferences, and his view of the distribution of possible wage offers facing him. As an individual lowers his minimum acceptable wage he will shorten his expected spell of unemployment, given that the distribution of wage offers from which he draws is unchanged. Hence, the more risk averse jobseeker, by lowering his reservation wage, will have to search a shorter period of time, on average, to find an offer acceptable to him. The effect of wage dispersion on duration of unemployment (allowing for adjustment in the reservation wage) cannot be predicted in general from models of job search, despite the belief expressed (from Stigler (1962, p. 236) to Hall (1975, p. 324)) that this effect should be positive. However, when a rectangular wage offer distribution is posited, the intuitively appealing hypothesis (1) can be obtained from a static model of job search (for example, McCall's model (1970)). While the regression specification used in this study to test the two implications presented above was developed in the context of the job search theory, alternative theories could produce these results; hence, the empirical work discussed here is not seen as a test of the search theory.5 Instead, a negative relationship between risk aversion and duration of unemployment could reflect a tendency for individuals to choose occupations and industries with patterns of employment suiting their risk preferences. And a positive association between dispersion in potential wages and duration may